Effect of Sm3+ as co-dopant in CaSO4:Dy,P TLD phosphor - Wani, J A; Dhoble, N S; Dhoble, S J (Recent Research in Science and Technology, 2012)
CaSO4: Dy,P and CaSO4:Dy,P,Sm thermoluminescence (TL) phosphors have been prepared by acid method and their TL glow curves and photoluminescence (PL) excitation and emission spectra are recorded. PL emission bands at 565, 599 and 613 nm were observed for CaSO4: Dy,P,Sm under the excitation wavelength 402 nm. Dosimetric peak is observed around 2460C at high temperature. Co-doping of Sm3+ in CaSO4:Dy,P enhances its TL intensity by a factor of 1.11.